2017
DOI: 10.1080/15563650.2017.1377839
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal bupropion ingestions in adolescents: increased morbidity compared with other antidepressants

Abstract: Adolescents who overdose on a single medication in a suicide attempt with bupropion have a statistically significant higher incidence of major outcomes and seizures. The risks of bupropion as a potential means of suicidal gesture by overdose must be considered, and weighed against its benefits and side effect profile when choosing an appropriate agent for the treatment of depression in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
(20 reference statements)
1
6
0
2
Order By: Relevance
“…Sheridan et al conducted a study that also used NPDS data to compare adolescent poison center cases involving exposure bupropion to those involving tricyclic antidepressants, although during a slightly different time-period and allowing co-ingestion of ethanol. 8 Their study had many similar findings to ours, including higher rates of hallucinations, seizures, tachycardia, and vomiting in the bupropion cases. Another similarity was the overall finding that bupropion cases were more likely to have MMD outcomes and need for hospitalization when compared to either TCA or SSRI cases.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Sheridan et al conducted a study that also used NPDS data to compare adolescent poison center cases involving exposure bupropion to those involving tricyclic antidepressants, although during a slightly different time-period and allowing co-ingestion of ethanol. 8 Their study had many similar findings to ours, including higher rates of hallucinations, seizures, tachycardia, and vomiting in the bupropion cases. Another similarity was the overall finding that bupropion cases were more likely to have MMD outcomes and need for hospitalization when compared to either TCA or SSRI cases.…”
Section: Discussionsupporting
confidence: 81%
“…4 This is a major issue of interest to both medical and public health professionals, who have made it the focus of multiple studies. [4][5][6][7][8][9] As a result, in 2004, the FDA added a black box warning to prescribing information for all antidepressants noting increased risk of suicide in children, adolescents, and young adults. 10 It has been suggested that adolescents who attempt suicide may have greater impulsivity than their non-suicidal peers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is approved as a medication for treatment in MDD, seasonal depressive disorders and smoking‐cessation therapy (Brunen, Vincent, Baumann, Hiemke, & Havemann‐Reinecke, ; Wille et al, ). It shows fewer unwanted side effects like weight gain or sedation (Horst & Preskorn, ; Laib, Brunen, Pfeifer, Vincent, & Hiemke, ) and consequently its use is increasing (Sheridan, Lin, & Horowitz, ). In Germany, the increasing number of defined daily doses from 2015 to 2016 (+12.8%) demonstrated the growing importance of the drug (Schwabe et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, the increasing number of defined daily doses from 2015 to 2016 (+12.8%) demonstrated the growing importance of the drug (Schwabe et al, ). Nevertheless, in cases of bupropion overdosing in 13–19 year old patients there was a higher percentage of serious outcomes and hospitalizations compared with tricyclic antidepressants (Sheridan et al, ), and also suicides by overdosing with bupropion have been reported (Mercerolle, Denooz, Lachatre, & Charlier, ; Sheridan et al, ). Additionally, dose‐dependent effects of lowering the seizure threshold have been described for bupropion (Dersch, Zwernemann, & Voderholzer, ).…”
Section: Introductionmentioning
confidence: 99%